2021
DOI: 10.1002/adfm.202102124
|View full text |Cite
|
Sign up to set email alerts
|

Dopant Engineering for Spiro‐OMeTAD Hole‐Transporting Materials towards Efficient Perovskite Solar Cells

Abstract: One of the most prominent hole‐transporting material (HTM) for hybrid perovskite solar cells has been 2,2″,7,7″‐tetrakis[N,N‐di(4‐methoxyphenyl)amino]‐9,9′‐spirobifluorene (spiro‐OMeTAD), which is commonly doped with metal bis(trifluoromethylsulfonyl)imide (M(TFSI)n) salts that contribute to generating the active radical cation HTM species. The underlying role of the metal cation, however, remains elusive. Here, the effect of metal cations (M = Li, Zn, Ca, Cu, and Sc) on doping spiro‐OMeTAD is analyzed by a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 35 publications
2
63
0
1
Order By: Relevance
“…In the broader context of research performed recently addressing stability issues, at the first glance, results reported in this publication would seem to contradict them. However, if we look at the device stability curves presented in the research articles describing PSCs containing doped spiro-OMeTAD, for example, Christians et al, 44 Seo et al, 45 and Kong et al, 46 there is a slow but consistent decrease in device performance. This drop in performance can be attributed to more than one factor; however, it does not eliminate the prospect that processes described in this publication are also playing a role.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In the broader context of research performed recently addressing stability issues, at the first glance, results reported in this publication would seem to contradict them. However, if we look at the device stability curves presented in the research articles describing PSCs containing doped spiro-OMeTAD, for example, Christians et al, 44 Seo et al, 45 and Kong et al, 46 there is a slow but consistent decrease in device performance. This drop in performance can be attributed to more than one factor; however, it does not eliminate the prospect that processes described in this publication are also playing a role.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is attributed to more fluorine content in LiPFSI, which not only increases hole extraction/transfer and improves film-forming capability of spiro-OMeTAD, but also reduces the recombination rate and trap density in the perovskite film. Except for lithium salt, other metal salts have been employed to improve the properties of spiro-OMeTAD and its HPSCs, such as AgTFSI, 518 Zn (TFSI) 2 , [519][520][521] Ca(TFSI) 2 , 519,522 Cu(TFSI) 2 , 519,523 MgTFSI 2 , 522 and Sc(TFSI) 3 . 519 The second kind of additives is the organic material, such as tBP, 524,525 PFPPY, 526 BMPyTFSI, 527 and pyridine.…”
Section: Spiro-ometadmentioning
confidence: 99%
“…Özellikle son yıllarda oldukça popüler bir araştırma alanı olan perovskite güneş hücrelerinin slot-die tekniği ile üretimi literatürde önemli bir yer tutmaktadır. Bilindiği gibi perovskite güneş hücreleri alttaş, elektron transfer tabakası, aktif soğurucu tabaka, boşluk transfer tabakası ve metal üst elektrot olmak üzere farklı tabakaların sandviç modelinde bir araya getirilmesi ile oluşmaktadır [38][39][40]. Bu tabakalardan elektron transfer tabakası perovskite hücre teknolojisinde aygıt performansı üzerinde önemli bir etkiye ve fonksiyona sahiptir.…”
Section: Introductionunclassified